2017
DOI: 10.1139/apnm-2016-0585
|View full text |Cite
|
Sign up to set email alerts
|

The Rab-GTPase activating protein, TBC1D1, is critical for maintaining normal glucose homeostasis and β-cell mass

Abstract: Tre-2/USP6, BUB2, cdc16 domain family, member 1 (TBC1D1), a Rab-GTPase activating protein, is a paralogue of AS160, and has been implicated in the canonical insulin-signaling cascade in peripheral tissues. More recently, TBC1D1 was identified in rat and human pancreatic islets; however, the islet function of TBC1D1 remains not fully understood. We examined the role of TBC1D1 in glucose homeostasis and insulin secretion utilizing a rat knockout (KO) model. Chow-fed TBC1D1 KO rats had improved insulin action but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In the current study, we have shown that TBC1D1 ablation results in impaired glucose tolerance, which is consistent with previous reports implicating this protein in maintaining beta cell mass (26,27). However, the current work also demonstrates that TBC1D1 is not required for intracellular GLUT4 trafficking in response to insulin as there were no differences in ITT or in total or phosphorylated (Ser-473) Akt2 or plasma membrane GLUT4 content.…”
Section: Tbc1d1 Ko Animals Display Intact Insulin Signalingsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, we have shown that TBC1D1 ablation results in impaired glucose tolerance, which is consistent with previous reports implicating this protein in maintaining beta cell mass (26,27). However, the current work also demonstrates that TBC1D1 is not required for intracellular GLUT4 trafficking in response to insulin as there were no differences in ITT or in total or phosphorylated (Ser-473) Akt2 or plasma membrane GLUT4 content.…”
Section: Tbc1d1 Ko Animals Display Intact Insulin Signalingsupporting
confidence: 92%
“…Given the unaltered GLUT4 content in this KO model and the proposed role of TBC1D1 in glucose homeostasis, we first examined the effect of ablating this protein on glucose handling at the whole-body level. In support of previous work demonstrating that TBC1D1 influences beta cell mass/stability (26,27), TBC1D1 KO animals displayed impaired glucose clearance during an intraperitoneal glucose tolerance test (GTT) ( Fig. 2A) as demonstrated by an increase in the area under the curve (p Ͻ 0.05; Fig.…”
Section: Skeletal Muscle Response To Insulinsupporting
confidence: 88%
“…This gene plays a significant role in cellular functions in mammals, and defects of which are closely associated with various disease processes (Shi et al, 2018). Besides, Paglialunga et al (2017) established a vital role for CDC16 in maintaining in vivo β-cell mass. This gene may have a similar function in chickens and could be a promising gene for Ab response for ND in chickens.…”
Section: Possible Causal Variant For Antibody Response To Newcastle Disease In Indigenous Chicken In Rwandamentioning
confidence: 99%
“…In addition, recent work from our laboratory has also shown that TBC1D1 knockout (KO) rats display a 34% reduction in β‐cell mass concomitant with dramatic reductions in insulin secretion and glucose tolerance, all of which are indicative of a diabetic phenotype (Paglialunga et al . ). Interestingly, TBC1D1 has recently been identified within the left ventricle (Quan et al .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, recent work from our laboratory has also shown that TBC1D1 knockout (KO) rats display a 34% reduction in β-cell mass concomitant with dramatic reductions in insulin secretion and glucose tolerance, all of which are indicative of a diabetic phenotype ). Interestingly, TBC1D1 has recently been identified within the left ventricle (Quan et al 2015;Stockli et al 2015;Paglialunga et al 2017) and, although the functional consequence of TBC1D1 within the heart remains unknown, the expression of this protein increases following an acute infarction, suggesting it represents a biologically relevant protein within this tissue (Quan et al 2015). Moreover, because genetic and pharmacological attenuations in insulin signalling and fatty acid oxidation impair cardiac function, induce dilated cardiomyopathy and increase mortality rates (Belke et al 2002;Augustus et al 2006;Tuunanen et al 2006;DeBosch et al 2006a;DeBosch et al 2006b;Laustsen et al 2007;Chang et al 2010), determining the functional role of TBC1D1 within the heart may have clinical relevance for understanding the development of diabetic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%